The Philippine Islands, 1493-1898, Vol. [10] 1597-1599 - Blair, Emma Helen 1911; Robertson, James Alexander 1873-1939; Bourne, Edward Gaylord 1860-1908 (IgLibrary], 1903)
[The present volume covers the years 1597-1599, and is mainly occupied with the details of the Philippine colony's internal affairs and development Mindanao has been conquered, but proves to be an unprofitable possession, except that the Spanish garrison there serves as a check on the piratical Moros, who otherwise would harry the Pintados Islands. Japanese pirates have menaced Luzon, and the Chinese immigration needs frequent restriction]